2019
DOI: 10.1017/s0954579419000427
|View full text |Cite
|
Sign up to set email alerts
|

Stationary and ambulatory attention patterns are differentially associated with early temperamental risk for socioemotional problems: Preliminary evidence from a multimodal eye-tracking investigation

Abstract: Behavioral Inhibition (BI) is a temperament type that predicts social withdrawal in childhood and anxiety disorders later in life. However, not all BI children develop anxiety. Attention bias (AB) may enhance the vulnerability for anxiety in BI children, and interfere with their development of effective emotion regulation. In order to fully probe attention patterns, we used traditional measures of reaction time (RT), stationary eye-tracking, and recently emerging mobile eye-tracking measures of attention in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 125 publications
(239 reference statements)
0
40
0
Order By: Relevance
“…Second, the literature should move away from reaction time-based difference scores, as they can exacerbate measurement error 53 . On this point, recent reviews focused on adults 54 and children 10 suggest that measures more proximal to the processing of salient stimuli, captured via functional magnetic resonance imaging (fMRI), event-related potentials (ERPs), or eye-tracking have more robust psychometric properties. In the current study, the use of eye-tracking across multiple measures incorporates both recommendations, while having the added bonus of being developmentally appropriate for use starting in the first months of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the literature should move away from reaction time-based difference scores, as they can exacerbate measurement error 53 . On this point, recent reviews focused on adults 54 and children 10 suggest that measures more proximal to the processing of salient stimuli, captured via functional magnetic resonance imaging (fMRI), event-related potentials (ERPs), or eye-tracking have more robust psychometric properties. In the current study, the use of eye-tracking across multiple measures incorporates both recommendations, while having the added bonus of being developmentally appropriate for use starting in the first months of life.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of different attention tasks across studies have failed to provide consistent results. Emerging research suggests that patterns of affect-biased attention across tasks within individuals may better capture relations with anxiety and anxiety risk 10 , 11 . Thus, it is important for researchers to examine relations between multiple attentional mechanisms captured by different tasks within a single sample 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the other end of the age spectrum, Isaacowitz and colleagues (2015) found no difference in bias to positive valence if selecting from the environment with MET, although SET studies had consistently shown a positivity bias for older adults. And, in between, Fu, Nelson, Borge, Buss, and Pérez-Edgar (2019) had 5- to 7-year-old children complete a standard attention-bias task with reaction time and SET measures. The same children also engaged in a standardized interaction with an adult stranger (modified from Buss, 2011).…”
Section: What Are We Beginning To Learn With Met?mentioning
confidence: 99%
“…One of the first studies to apply mobile eye tracking to motor processes and movement in infants. Fu, X., Nelson, E. E., Borge, M., Buss, K. A., & Pérez-Edgar, K. (2019). (See References).…”
Section: (Interim) Conclusionmentioning
confidence: 99%